IMPLEMENTASI GAMIFIKASI PADA PEMBELAJARAN BERPIKIR KOMPUTASIONAL SEBAGAI UPAYA PENINGKATAN HASIL BELAJAR SISWA - Damayanti, Masyita; Handayani, Anik Nur; Srini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the effectiveness of a gamification-based learning model in enhancing students’ learning outcomes in the subject of Computational Thinking. The research background highlights the persistent use of conventional instructional methods in Informatics education, which has led to low student engagement, limited creativity, and underdeveloped critical thinking skills. The study employed a quantitative approach with a quasi-experimental design using a One Group Pretest-Posttest model. The research subjects consisted of 30 seventh-grade students at SMP Negeri 22 Malang during the 2024/2025 academic year, selected through purposive sampling. The research instruments included learning achievement tests validated through expert judgment, validity testing, and reliability analysis. Data were analyzed using the Shapiro-Wilk normality test, paired sample t-test, and N-Gain analysis. The results indicated a statistically significant difference between pretest and posttest scores (p < 0.05), with an average N-Gain score of 0.33, categorized as moderate. These findings suggest that the implementation of a gamification-based learning model is moderately effective in improving student learning outcomes, particularly in developing Computational Thinking competencies.